Evaluation of antioxidant properties from purple tubers and their ability to improve glucose and lipid metabolism in streptozotocin-induced diabetic rats - Abdul Gofur; Siti Nur Arifah; Mochammad Fitri Atho'illah; Esha Ardiansyah; Nur Alfi Maghfirotus Sa'adah; Clara Kartika Aprilia Pratiwi; Khoirum Mawarti; Agung Witjoro; Sri Rahayu Lestari; Shofiyatul Mas'udah; Mardiana Lelitawati (Elsevier, 2024)
Background: Purple tubers have been used as a rich-nutrition source and are believed to have antioxidant properties. Objectives: The research aimed to evaluate the computational modelling and antioxidant activity of purple sweet potato (PSP), purple yam (PY), and taro. The selected tuber was then evaluated by in vivo experiment using streptozotocin-induced diabetic rats. Material and methods: Molecular docking of α-glucosidase, dipeptidyl peptidase 4 (DPP4), and 3‑hydroxy-3-methylglutaryl coenzyme-A reductase (HMGCR) protein was examined with various active compounds in PSP, PY, and taro. Antioxidant activity was measured using 2,2-diphenyl-1-picryhydrazyl (DPPH). The highest activity of antioxidant was then continued as treatment in streptozotocin (STZ)-induced diabetic rats. Results: Protein-ligand docking demonstrated that the amino acid residues of α-glucosidase, DPP4, and HMGCR with drug control also appeared in purple tubers active compounds. Antioxidant activity of PSP were higher (77.23 %) than PY (32.22 %) and taro (14.72 %). In diabetic rats, the blood glucose level, serum glutamic oxaloacetic transaminase (SGOT), serum glutamic oxaloacetic transaminase (SGPT), low-density lipoprotein (LDL), total cholesterol (TC), and triglyceride (TG) was higher than normal group while high-density lipoprotein (HDL) levels decreased. The number of hepatic necrosis cells and tumor necrosis factor α (TNF-α) increased compared to normal group, while PSP extract showed a significant decrease in blood glucose, SGOT, SGPT, LDL, TC, and TG and increased HDL. Proinflammatory cytokine TNF-α also decreases following the improvement of hepatic cells structure. Conclusion: Purple tubers could be an alternative treatment for hyperglycemia and hyperlipidemia. Purple tubers, especially PSP, have high antioxidant activity and can be promising as an antidiabetic agent.